Child Mental Health Education After The Covid-19 Pandemic - Dita Kurnia Hati; Bayu Eko Broto; Azidin Harahap (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The Covid-19 pandemic is a disease outbreak that has spread not only in Indonesia but throughout the world. This virus not only affects our physical health but also affects our mental health. Even though the government has now declared Indonesia to be free of masks, it cannot be denied that the coronavirus is still among us. For this reason, it is important to maintain good physical and mental health. During the pandemic, many people feel the consequences, especially children who still don't understand what is going on. In addition, the lack of awareness of us or our parents about mental health is a problem that must be faced. Mental health is a condition when our mind is peaceful and calm, so we can live a good life too, while children's mental health is related to how children face the challenges that exist in their lives. Community Service (PKM)